Metastable crystalline phase formation in deep eutectic systems revealed by simultaneous synchrotron XRD and DSC. Issue 73 (13th August 2020) - Hall, Charlie L.; Potticary, Jason; Hamilton, Victoria; Gaisford, Simon; Buanz, Asma; Hall, Simon R.
Abstract : For the first time, simultaneous pXRD and DSC is used to investigate the crystallinity of deep eutectic solvents upon cooling. Abstract : The phase behaviour of various deep eutectic systems was analysed using concurrent synchrotron powder X-ray diffraction and differential scanning calorimetry. Deep eutectic systems containing the pharmaceuticals metacetamol, 2-ethoxybenzamide or benzamide as binary mixtures with phenol revealed new crystalline phases melting either before or with crystals of phenol, highlighting their lower stabilities. Furthermore, in the phenol : 2-ethoxybenzamide system it was shown that multiple metastable phases can form, highlighting the potential for the separation of a hierarchy of crystal structures with differing stabilities from eutectic systems. Through these experiments, we strengthen the idea that eutectic systems can be described by understanding the formation and stabilities of metastable co-crystalline structures. These novel results lead to a deeper understanding of the structure and thermodynamics of deep eutectic solvents, with relevance for analagous systems across materials science.